Gemcitabine and S-1 combination chemotherapy versus gemcitabine alone for locally advanced and metastatic pancreatic cancer: a meta-analysis of randomized controlled trials in Asia. (August 2015) - Li, Yanxun; Sun, Jinjin; Jiang, Zhijia; Zhang, Linqiang; Liu, Geng
Abstract : Introduction: After decades of research, pancreatic cancer is still a devastating disease. The aim of this article was to assess the efficacy and safety of combination chemotherapy with gemcitabine (GEM) and S-1 (GS) therapy compared with GEM alone therapy in patients with locally advanced or metastatic pancreatic cancer. Methods: Relevant trials were identified by searching databases. Five trials were selected in this article. The indicators we used were overall response rate, disease control rate, 1-year survival rate and haematological toxicities. Results: Meta-analysis of the pooled data demonstrated that the overall response rate (risk ratio, RR = 2.52, 95% confidence interval, CI: 1.85–3.42, P < 0.00001) and disease control rate (RR = 1.24, 95% CI: 1.12–1.37, P < 0.0001) were significantly different for the GS and GEM alone chemotherapies. Among the group of patients, 43.4% in the GS group and 31.4% in the GEM group survived more than a year. According to this, patients who use the GS regiment may have a better prognosis than the GEM regiment (RR = 1.62, 95% CI: 1.12–2.33, P = 0.04). The combination chemotherapy with GEM and S-1 group had higher haematological toxicities including neutropaenia (RR = 1.58, 95% CI: 1.17–2.14, P = 0.003) and thrombocytopaenia (RR = 1.85, 95% CI: 1.28–2.67, P = 0.001). The incidence of anaemia was much the same in the two groups (RR = 1.22, 95% CI: 0.87–1.70, P = 0.24). Discussion: Overall response rate and disease control rate as well as 1-year survival rate in patients who received GS were superior to those treated with GEM alone. Combination chemotherapy with GEM and S-1 may offer greater benefits in the treatment of pancreatic cancer than GEM alone, although the GS group had higher haematological toxicities. Combination chemotherapy with GEM and S-1 might be an option of first-line chemotherapy for pancreatic cancer patients, at least in Asia. Mini Abstract: This systematic review analysing randomized controlled trials (RCTs) comparing S-1 combination chemotherapy versus GEM alone for locally advanced and metastatic pancreatic cancer demonstrated greater efficacy for S-1 combination in term of response, disease control and 1-year survival proportion.